O Youtube como ferramenta de estudo para o exame de suficiência em contabilidade - Galvão, Nadielli Maria dos Santos (2019)
The objective of the present study was to identify the most discussed themes in the channels of YouTube that aimed to assist students and bachelors in the preparation for the Examination of Sufficiency. For this, a descriptive research was carried out, analyzing the content of the videos made available on the selected plaƞ orm. It was verifi ed that the channels gave priority to the videos of resolution of questions of previous tests, not making available, to a great extent, the exposition of subjects of the accounting area aiming at a more complete thoroughness of the subjects. The results of the present work can support students of accounting sciences and bachelors interested in carrying out the evaluation of the Federal Accounting Council to understand what kind of content they will have access to in the Youtube channels directed to the exam under analysis. At the same time, it can help accounting faculty check the possibility of aggregating such resources in the teaching of their courses.